Grammatical information in the Russian-German and German-Russian dictionaries compiled in Germany in the 19th century - L.I. Akhmetsagirova; L.I. Gimatova (Ученые записки Казанского университета: Серия Гуманитарные науки, 2021)
The paper presents the results of a study of the grammatical information provided in the Russian-German and German-Russian dictionaries compiled in Germany during the 19th century. In the course of the comparative research, we studied the bilingual Russian-German and German-Russian dictionaries for the extent of elaboration and presentation of symbolic and factual paradigmatic characteristics, as well as syntagmatic information. A relationship between the dictionary type and the quality/quantity of grammatical information was found. Numerous examples proving that grammatical information in the pocket dictionaries is least elaborated were provided. For the complete and manual dictionaries, a tendency to an increase in the quality/quantity of their characteristics was noted. It was also demonstrated that the grammatical information for the Russian items of the Russian-German and German-Russian dictionaries is slightly more elaborated than for the German ones, thereby indicating that the main target audience of these dictionaries was still German-speaking users. Based on the results of our research, it was concluded that all the studied dictionaries show certain features in their structures. Therefore, special works devoted to the study of each dictionary separately are of scientific interest. Such works may be helpful in identifying the lexicographic value of the dictionaries, as well as the contribution made by their authors to the development of the Russian-German and German-Russian lexicography.